The Large Dendritic Morphologies in the Antoniadi Crater (Mars) and Their Potential Astrobiological Significance - Fabio Vittorio De Blasio (Geosciences, 2022)
Mars has held large amounts of running and standing water throughout its history, as evidenced by numerous morphologies attributed to rivers, outflow channels, lakes, and possibly an ocean. This work examines the crater Antoniadi located in the Syrtis Major quadrangle. Some parts of the central area of the crater exhibit giant polygonal mud cracks, typical of endured lake bottom, on top of which a dark, tens of kilometers-long network of dendritic (i.e., arborescent) morphologies emerges, at first resembling the remnant of river networks. The network, which is composed of tabular sub-units, is in relief overlying hardened mud, a puzzling feature that, in principle, could be explained as landscape inversion resulting from stronger erosion of the lake bottom compared to the endured crust of the riverine sediments. However, the polygonal mud cracks have pristine boundaries, which indicate limited erosion. Furthermore, the orientation of part of the network is the opposite of what the flow of water would entail. Further analyses indicate the similarity of the dendrites with controlled diffusion processes rather than with the river network, and the presence of morphologies incompatible with river, alluvial, or underground sapping processes, such as overlapping of branches belonging to different dendrites or growth along fault lines. An alternative explanation worth exploring due to its potential astrobiological importance is that the network is the product of ancient reef-building microbialites on the shallow Antoniadi lake, which enjoyed the fortunate presence of a heat source supplied by the Syrtis Major volcano. The comparison with the terrestrial examples and the dating of the bottom of the crater (formed at 3.8 Ga and subjected to a resurfacing event at 3.6 Ga attributed to the lacustrine drape) contribute to reinforcing (but cannot definitely prove) the scenario of microbialitic origin for dendrites. Thus, the present analysis based on the images available from the orbiters cannot be considered proof of the presence of microbialites in ancient Mars. It is concluded that the Antoniadi crater could be an interesting target for the research of past Martian life in future landing missions.